Byron and Nineteenth-Century Literary Philhellenism in America - Maria Schoina (European Journal of American Studies)
This essay traces Byron’s presence in early nineteenth-century American culture and his extensive influence on philhellenic poetry written during and after the Greek Revolution. After exemplifying how Byron’s philhellenic verse read throughout Europe made him the champion of modern Greece, I explore the ways Byron’s lines inspired a host of poets across the Atlantic. My discussion aims to demonstrate the American poets’ rich and diverse engagement with Byronic modes, hoping to bring a deeper understanding of the texts in question as well as of the historical frames surrounding them.